Upaya Peningkatan Minat Belajar Siswa Pada Pelajaran PAI Melalui Metode Index Card Match - Zaimi Maryati (MGMP PAI SMP BINTAN, 2023)
Seeing the low interest in student learning in the subject of Islamic Religious Education, which is caused by a lack of understanding of a material produced from learning delivered by the teacher is generally caused by the delivery of material using only lecture and rote methods, the lack of use of learning methods and the lack of supporting infrastructure learning and teaching activities. Therefore this paper aims to determine the level of student interest in Islamic education subjects. So the focus of this paper is what efforts are being made to find out students' interest in learning in the subject of Islamic Religious Education in class VIII SMP Negeri 9 Bintan. To answer this question, this paper uses action research. From the analysis of the data obtained, it shows that there was a significant increase in student learning interest after using the index card match learning method in Islamic Religious Education subjects compared to before the action was held. This shows that efforts to increase students' interest in learning by using the index card match method have proven effective in class VIII students of SMP Negeri 9 Bintan.